(untitled) (Res Medica, 2013)
TABLE OF CONTENTS ABDOMINAL CRISES III: I.S.R. Sinclair, F.R.C.S. THE BIOLOGY OF MONGOLISM: R.A. Bailey, M.B., Ch.B. RES MEDICA SOME ASPECTS OF FUNCTIONAL ORGANISATION IN THE CEREBRAL CORTEX: D.G. Hardy, B.Sc. THE APPEAL FUND CONGENITAL DISLOCATION OF THE HIP: P.J. Swarbrick, M.B., Ch.B.